"CORRELATION BETWEEN TRANSCUTANEOUS BILIRUBIN (TCB) AND TOTAL SERUM BILIRUBIN (TSB) IN PRETERM NEONATES” - MADIRALA, SPANDANA; KHER, ANJALI (International Journal of Psychosocial Rehabilitation, 2020)
Utility of TCB in preterm neonates (< 37 weeks gestation), and its use on neonates before phototherapy is not validated. Therefore, it is undertaken to find out the relation of TCB &TSB in preterm neonates before and during phototherapy. 1.To analyze the correlation between TCB readings at different areas such as forehead, sternum and pubic symphysis with TSB in preterm neonates before phototherapy. 2.To analyze the correlation between TCB readings on sternal region with TSB levels pre-phototherapy and during phototherapy in preterm neonates. 3.To determine correlation among the TCB & TSB levels of early & late preterm neonates. Preterm neonates satisfying the inclusion criteria with hyperbilirubinemia and treated by phototherapy are taken for the study with TCB levels and serum bilirubin levels measured and compared at different sites, then a photo resistant material is placed over sternum and TCB is measured over the same area before and during phototherapy, then there will be a comparison of these levels with serum bilirubin levels before and during phototherapy. TCB evaluation is almost similar to TSB evaluation in preterm neonates undergoing phototherapy hence it is a reliable indicator for assessment of hyperbilirubinemia. TCB is as reliable as TSB for assessment of hyperbilirubinemia.